Running in triangles: the effects of continuous and discrete locomotion techniques on spatial orientation in virtual reality - a comparative study - Brade, Jennifer; Stiens, Philipp; Melzer, Annegret; Korb, Samuel; Klimant, Franziska; Dix, Martin (Frontiers in Virtual Reality, 2026)
As we navigate in real-world environments, our egocentric location representations are seamlessly and automatically refreshed. However, when traversing a virtual space using magical locomotion techniques, it is common to experience disorientation and discomfort due to insufficient sensory input, particularly related to bodily movement. To avert disorientation and discomfort (cybersickness) in virtual reality without limiting overall usage by employing more natural locomotion techniques (redirected walking, treadmill, etc.), alternative approaches must be explored. In the presented experiment, participants engaged in a spatial updating task within a sparse virtual scene and were instructed to return to an initial position following simulated movements. They performed this task using the teleportation method, a purely continuous locomotion approach without self-motion (dash), and a combination of both techniques. All three methods were evaluated over short (3 m) and long (13 m) distances, and cybersickness along with cognitive load were assessed for every condition. Overall, the findings indicated no notable differences in cybersickness, cognitive load, and spatial localization across the conditions, although cognitive load was reduced and spatial localization was improved at shorter distances. For the selected scenario, the results suggest that the extent of continuous locomotion offers only a minimal advantage in spatial orientation and virtually no downside concerning cybersickness.